If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 3 = 6x + -9 Reorder the terms: 3 + -3x = 6x + -9 Reorder the terms: 3 + -3x = -9 + 6x Solving 3 + -3x = -9 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 3 + -3x + -6x = -9 + 6x + -6x Combine like terms: -3x + -6x = -9x 3 + -9x = -9 + 6x + -6x Combine like terms: 6x + -6x = 0 3 + -9x = -9 + 0 3 + -9x = -9 Add '-3' to each side of the equation. 3 + -3 + -9x = -9 + -3 Combine like terms: 3 + -3 = 0 0 + -9x = -9 + -3 -9x = -9 + -3 Combine like terms: -9 + -3 = -12 -9x = -12 Divide each side by '-9'. x = 1.333333333 Simplifying x = 1.333333333
| 6.5?4x= | | -12a=36 | | 108=-6x+8(4x+7) | | -3(c-2)-4=5-(c-1) | | 4x+6-7x=-8 | | .89=5.3n+9.5 | | 6-4=16-9d | | -3x+72=107+-10x | | 3x^2-7x-29=0 | | X=-7y+21 | | 5x-2(2x-8)=5(2x-7)+7x | | 0.5n=0.4+0.2n | | X+0.3x=100.00 | | -4b+9-7= | | 4x+5=5x-10 | | 8(x+3m+7)= | | -3(1+6r)=14+-r | | -4(x-4)+6=22 | | 12b-5c+5b+1= | | 16x+3y= | | 3[4+2(y-1)]=36 | | -4x+90=50 | | 7=5+2(7c+1) | | 4-12=5s+51 | | (50-2x)*x=200 | | (7+2)xX+1= | | 5x+61=73+2x | | -g=1.5g-3 | | m(x)=(3x-1)(3-x)+4x^3+19 | | y=(20+x)(3000-100x) | | -0.75x=0.86 | | (3-9x)= |